MODELING SLOPE-ASCENDING SIGHT DISTANCE FOR OVERTAKING MANOEUVRE IN DOUBLE LANE HIGHWAY (Journal of Experimental Research, 2016)
Many vehicles on the highway move at speeds below the design speed obviating overtaking maneuvers by vehicles that move at the design speeds. The paper is an attempt to formulate a model to determine the minimum overtaking sight distance to be maintained by the slope-ascending overtaking vehicle driver on an inclined double lane divided highway. The vehicle and road user characteristics as well as the vertical road geometry are combined to assess the overtaking distance by formulating a mathematical model that satisfies the laws of the mechanics of motion.